Modeling of Methane Hydrate Decomposition by Using Chemical Affinity - Farshad Varaminian; Zohreh Abbasi nia (Iranian Journal of Chemistry & Chemical Engineering, 2010)
In this work, experimental kinetics data of methane hydrate decomposition at temperatures ranging from 272.15 to 276.15 K and at pressures ranging from 10 to 30 bars were modeled by using chemical affinity. This model proposed a macroscopic model which is independent of any intermediate mechanism like heat or mass transfer. The results show there is good agreement with experimental data. Also the two parameters of model were calculated and correlation coefficient of model is higher than 0.9.